"They're Constantly Cycling Through": Lessons about Turnover and Collaborative Forest Planning. Issue 1 (30th October 2020) - Coleman, Kimberly J; Butler, William H; Stern, Marc J; Beck, Samantha L
Abstract: Within forest planning and management, collaboration has becoming increasingly widespread. Many collaborative projects take place over long time periods, and thus personnel turnover is inevitable within these groups. Scholars from the fields of business and organizational science have long studied strategies that organizations can use to prepare for and address turnover successfully. We draw from that literature and use it to examine the Collaborative Forest Landscape Restoration Program (CFLRP), a federal program aimed at bringing diverse stakeholders together to address the increasing costs, severity, and prevalence of wildfires in the United States. We conducted qualitative analysis of interviews, archival documents, and memos to explore what strategies are used within CFLRP groups to address turnover. We discuss our findings in light of the existing literature from business and organizational science and present insights about which strategies may be adaptable to collaborative natural resource management and which may require further research to assess their applicability to collaborative groups.